Rational Targeting of Cdc42 Overcomes Drug Resistance of Multiple Myeloma - Nguyen, Phuong; Chakrabarti, Jayati; Li, Yuan; Kalim, Khalid W.; Zhang, Mengnan; Zhang, Lin; Zheng, Yi; Guo, Fukun (Frontiers in Oncology, 2019)
Multiple myeloma (MM) drug resistance highlights a need for alternative therapeutic strategies. Here, we show that CASIN, a selective inhibitor of Cdc42 GTPase, inhibited proliferation and survival of Melphalan/Bortezomib-resistant MM cells more profoundly than that on Melphalan/Bortezomib-sensitive cells. And CASIN was more potent than Melphalan/Bortezomib in inhibition of Melphalan/Bortezomib-resistant cells. In addition, CASIN sensitized Melphalan/Bortezomib-resistant cells to Melphalan/Bortezomib. Mechanistically, Cdc42 activity was higher in Melphalan/Bortezomib-resistant cells than that in Melphalan/Bortezomib-sensitive cells. CASIN inhibited monoubiquitination of FANCD2 of the Fanconi anemia DNA damage repair pathway in Melphalan-resistant cells, but not in Melphalan-sensitive cells, sensitizing Melphalan-resistant cells to DNA damage. CASIN suppressed EGFR, STAT3 and ERK activities in Bortezomib-resistant cells to a larger extent than that in Bortezomib-sensitive cells. Reconstitution of ERK activity partially protected CASIN-treated Bortezomib-resistant cells from cell death, suggesting that CASIN-induced killing is attributable to suppression of ERK. Importantly, CASIN extended lifespan of mouse xenografts of Bortezomib-resistant cells and caused apoptosis in myeloma cells from Bortezomib-resistant MM patients. Finally, CASIN had negligible side effects on peripheral blood mononuclear cells from healthy human subjects and on normal B cells. Our data demonstrate a proof of concept that rational targeting of Cdc42 represents a promising approach in overcoming MM drug resistance.